It’s Not All That Money: Class in Jim Grimsley’s Comfort & Joy - Trušník, Roman (American & British Studies Annual, 2015)
Until recently, discussions of class were overshadowed by explorations of race, ethnicity, and gender in American literary and academic circles. One of the modern novels that daringly explores the ramifications of class is Jim Grimsley’s Comfort & Joy (1999), which portrays the budding relationship between two southern men which, to a large degree, is continually undermined by their belonging to different classes. Dan Crell is a hospital administrator, while Ford McKinney is a pediatrician in the same hospital. Moreover, while Dan comes from a low-class North Karolina family, Ford belongs to the Old Savannah aristocratic milieu. Class interferes not only in the men’s relationship with each other but also in their relationships with their families of origin. More important, the novel convincingly demonstrates that class is not only a matter of money but perhaps even more so of culture inbred in the family.